2022
DOI: 10.3390/nu14112334
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Obesity and Stunting among Brazilian Adolescents: A Multilevel Analysis

Abstract: (1) Background: The purpose of this study was to identify the prevalence of obesity and stunting among Brazilian adolescents and its associations with social determinants of health (individual, family, and school), grounded on the necessity of investigating the determinants of nutritional problems within this population. (2) Methods: A population-based survey was administered to 16,556 adolescents assessed by the 2015 National School Health Survey. Multivariate models of obesity and stunting were estimated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
(45 reference statements)
1
11
0
3
Order By: Relevance
“…(17) La frecuencia observada de casos de alteraciones en el estado nutricional en cuanto a sobrepeso y obesidad en adolescentes resultó superior a la informada por Latacunga Salazar (Ecuador) y Salcedo Távara (Perú). (16,17) De manera similar, Vale et al (18) hallaron un 10% de incidencia en una cohorte de 16556 adolescentes brasileños.…”
Section: Discussionunclassified
“…(17) La frecuencia observada de casos de alteraciones en el estado nutricional en cuanto a sobrepeso y obesidad en adolescentes resultó superior a la informada por Latacunga Salazar (Ecuador) y Salcedo Távara (Perú). (16,17) De manera similar, Vale et al (18) hallaron un 10% de incidencia en una cohorte de 16556 adolescentes brasileños.…”
Section: Discussionunclassified
“…The data collection technicians were instructed to take two weight and height measurements and to repeat the third one if the previous ones were different; however, only one piece of information for each variable was recorded on the student’s smartphone. Further information about the research can be found in the PeNSE 2015 publication [ 21 ] and in articles already published by the research group [ 12 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…This gender-related dichotomy suggests a significant effect observed in studies conducted to assess this population in Brazil including the Brazilian National School Health Survey (PeNSE) and the Cardiovascular Risk Study in Adolescents (ERICA). These studies did not identify direct associations between living overweight or obesity and having high nutritional risk dietary patterns [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Male adolescents, younger adolescents, and those with better socioeconomic status had a higher prevalence of obesity. 19 A cross-sectional study based on data from the Study on Cardiovascular Risk in Adolescents analyzed 2530 adolescents aged 12 to 17 years who were enrolled in public and private schools in Belo Horizonte City, Brazil and showed that obesity was present in 7.21% of the sample. 20 Another study analyzed the temporal variation in the incidence of overweight and abdominal obesity among adolescents from public schools in a capital in northeastern Brazil.…”
mentioning
confidence: 99%
“…Through educational actions, schools can promote good practices and facilitate the guidance of healthy habits, in addition to providing spaces for oriented physical activity and increasing the pace of physical activities-from moderate intensity to vigorous-in physical education classes. 19,24 To the best of our knowledge, no studies have evaluated the benefits of physical exercise among poor Brazilian populations within the school environment. Thus, this study's results can be incorporated into school and health policies, allowing physical educators to carry out the recommendations of the WHO.…”
mentioning
confidence: 99%